2021
DOI: 10.1002/cjce.24280
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of hydrodesulphurization in industrial trickle bed reactor using mixing cell network approach

Abstract: A mixing cell network (MCN) was developed for the commercial diesel hydrodesulphurization process (DHDS) in a trickle bed reactor (TBR). The two-phase model is developed to simulate the performance of an industrial DHDS unit. Major hydrotreating reactions such as hydrodesulphurization (HDS), hydrodearomatization (HDA), and olefin saturation were accounted for in the developed model. The MCN model predictions on axial concentration profiles of sulphur, polynuclear aromatics (PNAs), monoaromatics (MAs), and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Yadav et al 29 reported kinetic modeling and simulation for the HDS of commercial diesel in a TBR by a mixing cell network approach to simulate the multiple reactions happening in industrial settings. Regarding the reaction conditions and reactor data to carry out the simulation, the temperature was 326 °C, with a H 2 to oil ratio of 314 Nm 3 /m 3 , 350 cm of diameter, and catalyst beds of the following heights: 295, 559, and 842 cm, respectively.…”
Section: Kinetic Models Based On Total Sulfur Concentrationmentioning
confidence: 99%
“…Yadav et al 29 reported kinetic modeling and simulation for the HDS of commercial diesel in a TBR by a mixing cell network approach to simulate the multiple reactions happening in industrial settings. Regarding the reaction conditions and reactor data to carry out the simulation, the temperature was 326 °C, with a H 2 to oil ratio of 314 Nm 3 /m 3 , 350 cm of diameter, and catalyst beds of the following heights: 295, 559, and 842 cm, respectively.…”
Section: Kinetic Models Based On Total Sulfur Concentrationmentioning
confidence: 99%